The real exchange rate, foreign aid and macroeconomic transmission mechanisms in Tanzania and Ghana - Katarina Juselius; Adbulaziz Reshid; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
A recent study of 36 sub-Saharan African countries found a positive impact of aid in the absolute majority of these countries. However, for Tanzania and Ghana, two major aid recipients, aid did not seem to have been equally beneficial. This paper singles out these two countries for a more detailed empirical investigation. The focus is now on the effect of aid when allowing external and nominal factors to play a role in the macroeconomic transmission mechanism. We conclude that aid played a significantly positive - but very different - role in the two countries. Due in part to generous aid inflows Tanzania experienced positive investment and GDP growth from the late 1960s to 2007. But, until the mid-1980s, the impact of aid on growth was well below its potential as the large inflows of aid facilitated a serious over appreciation of the real exchange rate. In Ghana, declining aid in the 1970s was associated with lacking growth while the reactivation of aid flows in the 1980s supported an economic rebound. When monetary and external factors are properly accounted for, we find that aid has been pivotal to growth in both real GDP and investment.
Keywords: C32; F35; O11; 330; foreign aid; Africa; transmission channels; unit roots; Cointegrated VAR; Tanzania; Ghana